The Comparison of the performance of crypto assets, stocks, bonds, and gold in Indonesia during Covid-19 Pandemic - Chandra, Vergo; Iryanto, M. Budi Widiyo (Jurnal Ekonomi Perusahaan, 2023)
This study aims to determine whether crypto assets are suitable as an alternative investment when compared to the performance of the LQ 45 stock index, 10-year Indonesian Government Bonds, and Antam's precious metal in the form of gold. The measurement of the performance of an investment is not only seen from the rate of return but also needs to pay attention to the risks to be borne, then the performance measurement is used using the Sharpe, Treynor, and Jensen measurement methods. The three models base their analysis on past rates of return to determine the compensation for the returns obtained for each measure of risk borne. This study used descriptive analysis with case study methods, while hypothesis testing was carried out by nonparametric statistical tests using Kruskal-Wallis H because there were more than two independent variables. The values of the Sharpe Index and Jensen Index show that Bitcoin investment instruments are the highest-performing instruments while the LQ45 stock index is the lowest. The conclusion of this study shows that there is no significant difference between investment performance using the Sharpe method, while in the Treynor and Jensen methods, there are significant differences.